Analisis Produktivitas Padi berdasarkan Indeks Kekeringan (NDWI dan NDDI) Lahan Sawah menggunakan Data Citra Sentinel-2A di Kecamatan Ambulu - Bowo Eko Cahyono; Rahmadin Rahagian; Agung Thahjo Nugroho (Department of Physics, Sebelas Maret University, 2023)
Rice is almost a staple food source for the world's population. The State of Indonesia contributes the largest amount of rice productivity, especially in the province of East Java. Ambulu District is part of the province of East Java, which has experienced a decline in rice productivity. The decline in rice productivity is thought to be the result of agricultural land drought. The purpose of this study was to determine the correlation value of the drought index (NDWI and NDDI) with rice productivity. This research was conducted using remote sensing methods using the Sentinel-2A satellite from 2016 to 2020 during the rainy season. Sentinel-2A satellite data is in the form of images, which are then cropped and digitized on agricultural land. Furthermore, the data was processed using Arcgis Software to obtain NDWI (Normalized Defense Water Index) and NDDI (Normalized Defense Drought Index) values as land dryness parameters, which were classified into 5 classes. The correlation results of the NDWI value on rice productivity have a directly proportional relationship with an effect of 61.96% and 38.04% influenced by other factors. The results of the correlation of NDDI values on rice productivity have an inverse relationship with an effect of 68.68% and 31.32% influenced by other factors